2019
DOI: 10.3390/ijms20215250
|View full text |Cite
|
Sign up to set email alerts
|

Coix Seed Extract Enhances the Anti-Pancreatic Cancer Efficacy of Gemcitabine through Regulating ABCB1- and ABCG2-Mediated Drug Efflux: A Bioluminescent Pharmacokinetic and Pharmacodynamic Study

Abstract: A deep insight into the function and kinetics of ATP-binding cassette (ABC) transporters may aid in the development of pharmaceutics that can minimize the particular facet of chemo-resistance. We utilized bioluminescence imaging to monitor the ABC transporter mediated intracellular drug efflux function. We also investigated the potential association between the intracellular bioluminescent pharmacokinetic profiles and the anti-tumor efficacy of the coix seed extract and gemcitabine against pancreatic cancer ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 52 publications
0
21
0
Order By: Relevance
“…14,15 Additionally, ceritinib can increase the intracellular concentration of cytotoxic agents in ATPbinding cassette transporter ABCB1-and ABCG2-overexpressing tumor cells by preventing drug efflux, potentially through competition for their substrate-binding site. 16,17 Since ABCB1/ABCG2 inhibition can increase the intracellular concentration of gemcitabine, 18 ceritinib may improve gemcitabine-based treatment efficacy regardless of the presence of oncogenic ALK or ROS1 fusions. Gemcitabine, taxanes and platinum analogs are active agents in multiple malignancies and are therefore an appropriate "backbone" to develop ceritinib-containing chemotherapy combinations.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Additionally, ceritinib can increase the intracellular concentration of cytotoxic agents in ATPbinding cassette transporter ABCB1-and ABCG2-overexpressing tumor cells by preventing drug efflux, potentially through competition for their substrate-binding site. 16,17 Since ABCB1/ABCG2 inhibition can increase the intracellular concentration of gemcitabine, 18 ceritinib may improve gemcitabine-based treatment efficacy regardless of the presence of oncogenic ALK or ROS1 fusions. Gemcitabine, taxanes and platinum analogs are active agents in multiple malignancies and are therefore an appropriate "backbone" to develop ceritinib-containing chemotherapy combinations.…”
Section: Introductionmentioning
confidence: 99%
“…Although various therapies have been developed against cancer, including chemotherapy, radiation therapy, and so forth, pancreatic cancer is still deadly and represents 10% of the five-year survival rate [75]. Resistance is known to occur in gemcitabine treatment, which is the most common anti-cancer drug [76,77]. The drug resistance makes gemcitabine ineffective, and it consequently leads to difficulties in the successful treatment of cancer.…”
Section: Resistance Inhibiting Natural Productsmentioning
confidence: 99%
“…Gemcitabine-induced ABC transporters were previously reported to cause drug resistance [76]. Qian et al demonstrated that coix seed extract downregulated the expression of ABCB1 and ABCG2 and induced sensitivity to gemcitabine.…”
Section: Resistance Inhibiting Natural Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is not only a commonly used TCM, but it is also a commonly consumed food. Coicis semen has been proven to have numerous functions, such as detoxification and dampness and arthralgia removal; it also reduces cancer risk ( Yu et al, 2011 ; Bai et al, 2018 ; Duan, 2018 ; Xu et al, 2018 ; Choi et al, 2019 ; Huang Q. et al, 2019 ; Huang Y. L. et al, 2019 ; Li et al, 2019 ; Liu H. Q. et al, 2019 ; Liu Y. N. et al, 2019 ; Manosroi et al, 2019 ; Qian et al, 2019 ; Zhang et al, 2019 ). Moreover, it has a wide range of anti-inflammatory, antioxidation, analgesic, and sedative effects, as well as pharmacological effects against gastric cancer, hepatocellular cancer, Lewis lung cancer, non-small cell lung cancer, pancreatic cancer, and pulmonary cancer (“Fuzheng” category represented by coicis semen oil) ( Manosroi et al, 2016a ; Manosroi et al, 2016b ; Qian et al, 2016 ; Xi et al, 2016 ; Wang et al, 2016 ; Han et al, 2017 ; Qu et al, 2017a ; Schwartzberg et al, 2017 ; Jang et al, 2018 ; Kim et al, 2018 ; Zhang et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%